The Purge of Civil Servants in Soviet Occupied Lithuania between June–December 1940 - Maslauskienė, Nijolė (Genocidas ir rezistencija, 2025)
Soviet occupation succeeded by annexation and the accession of the Lithuanian communists to power, the task of whom was to form a puppet Government and carry out the plans of the country's sovietisation, brought about the purge of civil servants. The officers of independent Lithuania were to be replaced by communists or other pro-Communist segments. However, the new power had to put up with the services of some officers before the regime trained its own cadres. Thus in 1940, the purge first of all affected high and middle rank civil servants politically and socially most hostile or unreliable to the new regime. The replacement of cadres was trusted exclusively to the personnel sections subordinate to the Communist Party's governing body, where the radical advocates of purge and non-Lithuanian communists prevailed. The scheme created conditions not only for the purge itself, but for the realization of group interests of communists too.The Lithuanian civil servants as early as August 1940, set out to different measures against the purge and the penetration of communists into administrative institutions, and thus demonstrated their political resistance to occupation regime and to the soviet system as such.
Keywords: Soviet occupation; collaborators; repressions; sovietization